Organization-Client Transactions and Organizational Governance Structures - Jones, Gareth R. (Academy of Management Journal, 1987)
Transaction cost theory was applied to an examination of how the characteristics of transactions between organizations and their clients affect internal organizational governance structures. The study assessed the effect of transaction costs on forms of organizational structure and control through two transaction characteristics, transaction uncertainty and performance ambiguity. The results suggest that when transaction uncertainty and performance ambiguity are high, organizations tend to be small and highly specialized and to adopt complex forms of task interdependence and employee control systems.